Food Handler’s Perception on Food Handling Course - Ismail, Lisa Mariam Syawal; Siti Hajar Zakariah; Nor Anis Intan AqiahTukiran; Adibah Aishah Md Sahak; Ainina Mastura Husin (Research and Innovation in Technical and Vocational Education and Training, 2021)
The main purpose of this study was to examine the perception level of awareness on food handling courses among food handlers and the factors that prevent them from attending the food handling course at Pasir Mas, Kelantan. A total of 59 food handlers who did not take the Food Handling Course were involved in this survey. The data obtained were analyzed using IBM Statistical SPSS software version 26. Preliminary studies were conducted showing that Cronbach’s alpha obtained was greater than 0.80. In general, the mean values of the two question items, the level of knowledge of the food handler and the factors that prevent the operator from attending the course of food handling, are at a moderate level. The analysis showed that there was a strong correlation between the level of awareness and the factors that prevented the food handler from attending a food handling course with p = 0.873> 0.005 In conclusion, food handlers must attend the food handling course by the government as a knowledge enhancement towards good hygiene and practices and prevention tools for food poisoning among customers.